HALAMAN MUKA MAJALAH TEMPO (Studi Analisis isi Perbedaan Halaman Muka Sebagai Representasi Tajuk Utama Majalah Tempo Edisi Tahun 1993/1994 dengan Tahun 2009/2010) - Lukman Nusa (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2016)
None of the magazine’s part which as important as its cover. The magazine covers determine the people’s first impression futhermore will influence their interest to read. For the press media who realize the importances, the covers will be designed as a simple but competitive and interesting design which representating the media’s philosophy.Futhermore, the theory of Environment states that until specific level, political system influences communication vise versa. This theory describes that the governement policy which is born in a political system, until a specific level, influences the news release. Base from the states, the problem of this research is the preference of Tempo the national news magazine’s news release which can be seen from its covers at two periods which has different political system’s characteristic in Indonesia.